Efficient synthesis and characterization of novel indolizines: exploration of in vitro COX-2 inhibitory activity and molecular modelling studies. (2nd March 2018) - Chandrashekharappa, Sandeep; Venugopala, Katharigatta N.; Tratrat, Christophe; Mahomoodally, Fawzi M.; Aldhubiab, Bandar E.; Haroun, Michelyne; Venugopala, Rashmi; Mohan, Mahendra K.; Kulkarni, Rashmi S.; Attimarad, Mahesh V.; Harsha, Sree; Odhav, Bharti
Abstract : Novel indolizine scaffolds as COX-2 inhibiting agents. Abstract : A series of novel indolizine scaffolds incorporating a cyano group at position 7 as potential cyclooxygenase (COX)-2 inhibitors has been synthesized and characterized by FT-IR, NMR, LC-MS, and elemental analysis. A molecular modelling study was carried out to explore the COX-2 binding properties of the synthesized compounds, in an endeavour to provide additional insights into the inhibitory potential to treat and/or manage inflammation and pain. All compounds demonstrated comparable docking scores with that of indomethacin, a potent nonsteroidal anti-inflammatory drug. Additional empirical scoring functions were also investigated to estimate the best ligand orientation into the binding site. Halogen atoms at the para position of the benzoyl ring at the third position of the indolizine nucleus showed promising COX-2 inhibitory activity. The observed promising activity was favoured by the ethyl moiety at the second position of the indolizine nucleus. These findings will provide insights into structural requirements for designing novel indolizine scaffolds as potent COX-2 inhibitors.